2017
DOI: 10.1016/j.envres.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to selenium and cadmium, fetal growth, and placental expression of steroidogenic and apoptotic genes

Abstract: Background Cadmium (Cd) and selenium (Se) antagonistically influence redox balance and apoptotic signaling, with Cd potentially promoting and Se inhibiting oxidative stress and apoptosis. Alterations to placental redox and apoptotic functions by maternal exposure to Cd and Se during pregnancy may explain some of the Cd and Se associations with fetal development. Objectives Investigate associations between Cd and Se concentrations in maternal toenails with placental expression patterns of tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 105 publications
(146 reference statements)
0
18
0
Order By: Relevance
“…At a molecular level, these findings are supported by evidence of toxic and essential metals interactions within the placenta. For example, antagonistic interactions between maternal toenail Cd and Se levels have been noted with respect to placental apoptotic gene expression [29]. Taken together, these results may suggest that individuals with low levels of essential metals may be more susceptible to the effects of toxic exposures on placental development and/or functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a molecular level, these findings are supported by evidence of toxic and essential metals interactions within the placenta. For example, antagonistic interactions between maternal toenail Cd and Se levels have been noted with respect to placental apoptotic gene expression [29]. Taken together, these results may suggest that individuals with low levels of essential metals may be more susceptible to the effects of toxic exposures on placental development and/or functioning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are known toxicokinetic and toxicodynamic interactions between toxic and essential metals [2527]. At an epidemiologic level, this has been demonstrated with respect to both placental functioning and preeclampsia, suggesting that essential metals may mitigate the relationship between toxic metals and preeclampsia [10, 28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, maternal Se concentrations and glutathione peroxidase (GPx) activity decrease [ 14 , 15 , 16 , 17 ]. Research shows, Se as well as cadmium (Cd) antagonistically work against oxidative stress by impacting redox balance and apoptotic signaling [ 18 ]. Deficiencies in Se were also linked to different diseases such as diabetes, heart disease, autoimmune disease, and even cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Everson et al performed a study evaluating the role of placental heavy metals (cadmium (Cd), arsenic (As), mercury (Hg), and lead (Pb)) as well as the essential trace elements zinc (Zn) and Se on the placenta. They showed that for placentas with low Zn and Se values, the weight of the placenta was also decreased [ 18 , 31 ]. Lewandowska et al showed that determining levels of Se after adjustment for other trace elements in early pregnancy (10th–14th week of gestation) still predicted well SGA newborns, which had reduced levels of Se in comparison with normal Se levels.…”
Section: Introductionmentioning
confidence: 99%
“…39 For example, exposure to metals, such as arsenic and cadmium, has also been associated with placental expression of genes related to hormone secretion and SGA status. 40, 41 Also, EDCs can inhibit human placental aromatase activity which produces estradiol from testosterone and stimulates placental growth. 42 It may be that exposure to EDCs or metals during pregnancy contributes to maladaptive fetal growth by disrupting the maternal and placental hormone levels.…”
Section: Discussionmentioning
confidence: 99%